Connection between micron-sized defects and dielectric strength of poly(dimethylsiloxane) elastomer films. (July 2022) - Fukui, Hiroshi; Tsuda, Takeaki; Kaminaga, Yoichi; Kim, Yoonyoung
Abstract: The quality of dielectric elastomer (DE) films is a key factor affecting the reliability of DE actuators. Reported here is the effect of the number of micron-sized defects on dielectric strength (DS) for poly(dimethylsiloxane) (PDMS) DE films. Using the same PDMS formulation but different procedures, we produced two model DE films with a thickness of approximately 50 μm. The two PDMS DE films suitably serve as a good-quality model film (EF1) and a low-quality model film (EF2) for this study, as shown by a large difference in the number of micron-sized defects found using micro-Raman techniques. The internal defects with various micron sizes in the two PDMS DE films can be quantitatively analyzed using an optical flaw inspection technique. According to two-parameter Weibull analysis, our assumption is that EF2 has a bimodal distribution of breakdown field ( E b ) consisting of failure mode 1 in the early failure range and failure mode 2 in the late failure range. The values of the electric field ( E ) at the failure probability of 63.2%, defined as the scale parameter and regarded as DS, are 76.3 V μm −1 for EF1, and 39.1 and 69.6 V μm −1 for EF2, respectively. For the E b distribution, the shape parameters estimated are 18.3 for EF1, and 4.7 and 10.2 for EF2, respectively. The results support the idea that there are different failure mechanisms between EF1 and EF2. The difference in the total number of internal defects, 12 for EF1 and 92 for EF2 per area of approximately 15 mm × 15 mm, should explain such a large variation in DS and E b distribution. Our findings show the beneficial use of the quantitative analytical approach for micron-sized defects associated with the quality control and premature breakdown of DE films. Highlights: Two model poly(dimethylsiloxane) (PDMS) dielectric elastomer (DE) films are prepared using the same formulation. The two PDMS DE films serve as a useful model film, each with a different number of micron-sized defects. Optical flaw inspection enables quantitative evaluation of the number of internal micron-sized defects in the PDMS DE films. The connection between the number of internal micron-sized defects and dielectric strength is useful for practical purposes.